Turn Taking in Teaching English at English Study Program of FKIP UKI Toraja - Normalia Sirande (UKI TORAJA, 2016)
This research attempted to reveal the types of turn taking, its function, and thestudents’ responses toward the use of turn taking signals in teaching English at EnglishStudy Program of FKIP UKI Toraja, Indonesia. This research employed descriptivequalitative method. This research used purposive probability sampling. Therespondents consisted of 3 lecturers and 15 students of English education StudyProgram. The data was collected by using observation, recording, and interviewing.The findings showed that 1) there were three types of turn taking signals which wasused by the lecturers in the interaction during teaching i.e. turn yielding signals, turntakingsignals, and turn claiming signals, 2) the signals were used for several functionsincluded to check the students’ understanding, to welcome the students, to thank thestudent and as a leave-taking, to correct the students’ answer, to get the students focuson the topic, to warn the students, and to stop the students for a further explanation,and 3) the students responded the given signals in both verbal and non-verbal signals.So, it was concluded that the classroom interaction in this research was still dominatedby the lecturer.